SecureID-HE: Homomorphic Encryption for Privacy-Preserving Digital Identity Verification - Suman Kumar Sanjeev Prasanna, Lauren VanTalia (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Preserving privacy in digital identity verification is increasingly critical as multi-institution systemsexchange sensitive biometric and behavioral data. Traditional verification approaches typically requiredecryption during computation, exposing raw templates to potential breaches and undermining trust in large-scale deployments. This research introduces SecureID-HE, a homomorphic encryption